Synovial fluid proteome profile of surgical versus chemical induced osteoarthritis in rabbits - Syed Sulaiman, Sharifah Zakiah; Tan, Wei Miao; Radzi, Rozanaliza; Shafie, Intan Nur Fatiha; Ajat, Mokrish; Mansor, Rozaihan; Mohamed, Suhaila; Rahmad, Norasfaliza; Ng, Angela Min Hwei; Lau, Seng Fong (PeerJ, 2022)
Background: Animal models are significant for understanding human osteoarthritis (OA). This study compared the synovial fluid proteomics changes in surgical and chemical induced OA models. Methods: Thirty rabbits either had anterior cruciate ligament transection (ACLT) procedure or injected intra-articularly with monosodium iodoacetate (MIA, 8 mg) into the right knee. The joints were anatomically assessed, and the synovial fluid proteins analyzed using two-dimensional polyacrylamide gel electrophoresis (2DGE) and MALDI TOF/TOF mass spectrometry analysis at 4, 8 and 12 weeks. The proteins' upregulation and downregulation were compared with control healthy knees. Results: Seven proteins (histidine-rich glycoprotein, beta-actin-like protein 2 isoform X1, retinol-binding protein-4, alpha-1-antiproteinase, gelsolin isoform, serotransferrin, immunoglobulin kappa-b4 chain-C-region) were significantly expressed by the surgical induction. They characterized cellular process (27%), organization of cellular components or biogenesis (27%), localization (27%) and biological regulation (18%), which related to synovitis, increased cellularity, and subsequently cartilage damage. Three proteins (apolipoprotein I-IV precursor, serpin peptidase inhibitor and haptoglobin precursor) were significantly modified by the chemical induction. They characterized stimulus responses (23%), immune responses (15%), biological regulations (15%), metabolism (15%), organization of cellular components or biogenesis (8%), cellular process (8%), biological adhesions (8%) and localization (8%), which related to chondrocytes glycolysis/death, neovascularization, subchondral bone necrosis/collapse and inflammation. Conclusions: The surgical induced OA model showed a wider range of protein changes, which were most upregulated at week 12. The biological process proteins expressions showed the chemical induced joints had slower OA progression compared to surgical induced joints. The chemical induced OA joints showed early inflammatory changes, which later decreased.